PENGARUH MODEL MAKE A MATCH BERBANTUAN MEDIA KAJEGA PADA MATERI GAYA TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 066053 T.A 2025/2026 - Fadillah Annisah; Lala Jelita Ananda; Winara; Imelda Free Unita Manurung; Syahrial (STKIP Subang, 2026)
This study aimed to determine the effect of the Make A Match learning model assisted by KaJeGa media (Kartu Jelajah Gaya) on the science learning outcomes of fourth-grade students on the topic Force in Everyday Life. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all fourth-grade students at UPT SDN 066053 Medan in the 2025/2026 academic year, totaling 37 students. The sampling technique used was total sampling, with class IV B as the experimental group and class IV A as the control group. Data were collected through observation, interviews, tests, and documentation. The research instrument was a multiple-choice test that had been validated and tested for reliability. Data analysis was conducted using descriptive and inferential statistics through the Independent Samples t-Test with the assistance of SPSS software. The results showed that the average pretest score in the experimental class increased from 51.58 to 81.32 in the posttest, while the control class increased from 44.17 to 73.17. The hypothesis testing results indicated a significance value of 0.014 < 0.05, which means there is a significant effect of the Make A Match learning model assisted by KaJeGa media on students’ science learning outcomes. Therefore, the Make A Match learning model assisted by KaJeGa media is effective in improving students’ learning outcomes on the topic of force.